A comprehensive data retrieval and correction approach from 40-nm flash memory with selective chemical engraving - Zeng, Xiaomei (2024)
Floating gate-based flash memory is a widely used storage medium for sensitive data that may be relevant to forensic investigations. For various data extraction techniques, the accuracy of the recovered data is critical to ensuring the integrity of information as forensic evidence. In cases where the devices are physically or digitally damaged, invasive data extraction techniques serve as a last resort, and can directly extract binary from individual memory cells. Here we introduce a new invasive data extraction technique called selective chemical engraving. This electrochemical-based approach could systematically imprint the data of ‘0’ and ‘1’ as cavities on memory surfaces, which can subsequently be imaged with an optical microscope and SEM. This technique is capable of extracting data stored in embedded flash memory in microcontrollers of 40 nm technology node with a high accuracy of 99.66%. The error correction code (ECC) stored in the flash memory was also extracted together with the data. By analysing the extracted ECC, we were able to accurately derive the error correction algorithm of single error correction-double error detection (SEC-DED). The reconstructed SEC-DED code was then used to correct all 0.34% of errors. The high data retrieval accuracy (99.66%) together with the error correction capability led to a 100% accuracy of recovered data. This selective chemical engraving approach offers a comprehensive solution for the lowest-level data retrieval and correction from 40 nm technology flash memory, providing a new avenue for forensic data extraction.